Quantifying Biofield Therapy through Biophoton Emission in a Cellular Model - Kent, Jeremy B; Li, Jin; Li, Xudong Joshua (Journal of Scientific Exploration, 2020)
Biofield therapy has shown positive results over a broad range of pathology from preclinical research to human studies. However, biofield therapy investigation is limited by an inability to quantify the therapeutic effect. This study aimed to measure the effects Reiki had on mice intervertebral disc (IVD) cells compared to sham and to quantify Reiki by measuring photon emission. We treated mice IVD cells with ten minutes sessions of either Reiki or sham on three successive days. During treatment, we placed the cells in a specifically constructed box with an installed photon multiplier tube (PMT). Reiki significantly increased the photon emission of the cells post-treatment compared to Reiki pretreatment and sham (P<0.05). Real time PCR showed an increase in collagen II and aggrecan (P <0.05). We present a means to quantify biofield therapy by measuring the post-treatment photon emission. We concurrently demonstrate Reiki’s effect on the anabolic healing response.